RNAi and small interfering RNAs in human disease therapeutic applications - Lares, Monica R. (2010)
Small interfering RNAs (siRNAs) have shown to effectively down-regulate gene expression in human cells, giving them potential to eradicate disease. Prospects for clinical applications are discussed in this review, along with an overview of recent history and our current understanding of siRNAs used for therapeutic application in human diseases, such as cancer and viral infections. Over recent years, progress has been made in lipids, ligands, nanoparticles, polymers and viral vectors as delivery agents and for gene-based expression of siRNA to enhance the efficacy and specificity of these methods while at the same time reducing toxicity. It has become apparent that given the recent advances in chemistry and delivery, RNAi will soon prove to be an important and widely used therapeutic modality.